HUBUNGAN ANTARA KONSUMSI MAKANAN KARIOGENIK DAN FREKUENSI GOSOK GIGI DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA 3-5 TAHUN DI TK NEGERI PEMBINA KECAMATAN MOJOROTO KOTA KEDIRI TAHUN 2017 - silvia, cindy; yanuaringsih, galuh pradian; lutfiasari, dessy (Universitas Kadiri, 2019)
Dental caries is a disease of dental tissue characterized by tissue damage and it is started from the surface extending towards the pulp. The cariogenic foods are the meals that able to cause dental caries. The cariogenic foods are the meals that able to cause dental caries. Also, the other factor that caused dental caries such as brushing teethwich is not in accordance with procedur. That survey result of 15 childerns who checked their teeth was 80% have caries and 20 % did not have caries. This research aims to discover between the cariogenic foods consumption and brushing teeth frequency by dental caries caused on 3 up to 5 year-old children at Pembina Elementary School Kediri City, Mojoroto Regency in 2017. The research design is using correlationanalytic by cross sectional oncoming. The population had been taken as many as 56 students. The samples were takenua much 50 students, applyingsimple random sampling. The data collection is appliedquestionnaire and observation, bivariate data analysis by using spearman rank and multivariate by using multiple logistic regressions. The result in this research is was showing that 69.9% of student attached dental karies, consuming cariogenik foods and rerely brushing teeth as much 75%. The bivariate analysis result is variable of cariogenic foods consumption had low events relation by dental caries caused whit its result p= 0.000 and correlation coefficient +0.621, while brushing teeth frequency also had strong relation with dental caries caused result P= 0.000 correlation coefficient +0.785. Bivariate analysis result which is influential but brushing teeth frequency result Exp(B) 3.008 fold influenced on dental caries. The conclusion that obtained from this research are decrease or confine cariogenic foods and brush teeth according to procedure which is an effort preventing the occurrence of dental caries.Keywords : cariogenic foods, brushing teeth frequency, dental caries